The Influence of Work Culture and Competence on Employee Performance with Commitment as an Intervening Variable at BPJS Employment Branch Offices in Medan Raya - Dionica Putri Tampubolon; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This research aims to analyze the influence of work culture and competency on employee performance with commitment as an intervening variable at BPJS Employment Branch Offices throughout Medan Raya. A quantitative approach was used in this research, with data collection through questionnaires distributed to employees as respondents. The data analysis technique uses the Partial Least Square (PLS) method to test direct and indirect relationships between research variables. The results of this research are as follows: Work Culture has a positive and significant effect on Employee Performance with an original sample value of 0.267 and ap value of 0.002. Work Culture has a positive and insignificant effect on Commitment with an original sample value of 0.110 and ap value of 0.153. Commitment has a positive and significant effect on Employee Performance with an original sample value of 0.298 and ap value of 0.016. Competency has a positive and significant effect on employee performance with an original sample value of 0.370 and ap value of 0.012. Competence has a positive and significant effect on Commitment with an original sample value of 0.804 and ap value of 0.000. Work Culture has a positive and insignificant effect on employee performance through Commitment with an original sample value of 0.033 and ap value of 0.173. Competence has a positive and insignificant effect on employee performance through Work Commitment with an original sample value of 0.240 and ap value of 0.027.